Physical characterization of 2009 WN25: exploring the link with November i-Draconids meteor shower. Issue 2 (23rd May 2019) - Ieva, S; Micheli, M; Perna, D; Popescu, M; Dotto, E; Mazzotta Epifani, E; Antoniucci, S; Fulvio, D; Brucato, J R; Poggiali, G; Barucci, M A; Perozzi, E
ABSTRACT: The distinction between active and inactive small bodies in the Solar System has become more blended in recent years, with the discovery of objects exhibiting a transient nature. The assumption of activity (past or present) for a small body can be achieved indirectly by its identification as the parent of a meteor shower. In this framework, the near-Earth object (NEO) 2009 WN25 represents an interesting case study. The target, recovered in 2015, is the likely progenitor of a complex stream of meteor shower, and its peculiar high-eccentricity, high-inclination orbit, with an aphelion as far as Jupiter, is responsible for the meteoroid long-term stability. We investigated the physical characteristics of 2009 WN25, by obtaining spectral observations from ESO-NTT and ESO-VLT to constrain its surface composition. We also compared the observed spectra with meteorite data present in the RELAB database and obtained from other laboratories. We found for 2009 WN25 a primitive D-type composition, in agreement with being a cometary progenitor. The low-albedo nature we derived implies a km-sized body, making it one of the few D-type NEOs in this size range. The two spectra we obtained have a similar spectral slope in the 0.5–0.9 μm range, suggesting a possible homogeneous surface. Finally, by comparison with meteorite data we found an association with an unaltered sample of the rare meteorite Tagish Lake. All these evidences strongly support the association with the meteoroid stream.